Cancer Patients’ Anxiety Are Negatively Correlated to Social Interaction Capability - Emilia, Silfi; Taufik, Agis; Mulyono, Wastu Adi (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background: Cancer is the leading cause of death in the world. Data shows the number of cancer deaths in the world reaches 10 million cases. Therefore, cancer patients often experience anxiety. However, anxiety can also stem from chemotherapy procedures and side effects. The literature says social interaction can overcome anxiety. This study aims to analyze the relationship between social interaction and anxiety levels of cancer patients undergoing chemotherapy at Prof. Dr. Margono Soekarjo Hospital. Method: This study used a cross-sectional study design. Sampling using an accidental sampling technique. A total of 107 respondents participated in this study. Anxiety was measured using the STAI-Trait questionnaire and social interaction using The RAND Health Social Battery questionnaire. Hypothesis was examined by r Pearson’s test. Results: The results showed that there was a negative significant relationship between social interaction and anxiety levels of cancer patients undergoing chemotherapy (r: -0.233; p: 0.1). Conclusion: There is a relationship between social interaction and anxiety among cancer patients.